Boundaries of the Firm: Insights From International Entry Mode Research - Brouthers, Keith D.; Hennart, Jean-François (Journal of Management, 2007)
Deciding on the boundaries of a firm as it expands abroad is a critical decision for managers. Despite the rapid growth in research addressing this issue, many questions remain unanswered. In this article, the authors review the international entry mode choice literature, identify weaknesses and shortcomings, and provide suggestions on how researchers can add to the knowledge of mode choice and help managers make better international boundary decisions.